Influence of electrolytes on the controlled release of verapamil hydrochloride from HPMC K15M matrix tablets - Vidyadhara, Suryadevara; Babu, Janga Ramesh; krishna, Talamanchi Bala; krishna, Talamanchi Bala (Asian Journal of Pharmaceutics (AJP), 2014)
Verapamil hydrochloride was formulated as oral-controlled release matrix tablets using hydrophilic polymer such as hydroxypropyl methylcellulose K15 M (HPMC 15 M) along with electrolytes. In this work a new attempt was made for in situ interactions between drug and electrolytes were devised to control the release of highly water soluble drugs from oral hydrophilic monolithic systems. Electrolytes such as aluminum hydroxide and sodium carbonate were used at different concentrations in various formulations, while drug and polymer concentrations were maintained constantly at 1:2 ratios in all the formulations. These electrolytes were used to monitor matrix swelling and gel properties. Electrolytes at higher concentrations exhibited greater inhibition in drug release from the matrix and low concentrations were accounted for controlled release of the drug.The results indicated that the drug released at a controlled rate were due to differential swelling rate and matrix stiffening, and provides a uniform gel layer.These findings indicated that the swelling and gel formation in the presence of ionizable species within the hydrophilic matrices provide an attractive alternative for controlled drug delivery from a simple monolithic system. Accelerated stability studies were carried out as per ICH guidelines for some selected formulations, which indicated that these formulations were stable at accelerated storage conditions.